Investigações psicanalíticas sobre realidade e cultura: o conceito de fantasia ideológica em Žižek - Silva, Karinny Gonçalves da (2024)
Based on Freudian and Lacanian constructions, Slavoj Žižek seeks to contribute, through his concept of ideological fantasy, to the debate on reality and how humans apprehend it, relate to it, modify it and affect it. From this perspective, this paper aims to investigate the concept of ideological fantasy in order to contribute to discussions on the relationship between subject, culture and reality through psychoanalysis. Through a reading of the works of Althusser, Lacan and Freud, it is proposed to write about the importance of these authors for the concept of ideological fantasy proposed by the Slovenian philosopher. Considering fantasy as an imaginary scene that enables the subject to structure their desire and their relationships with objects, Žižek takes this process to the level of the signification of socially shared reality, producing a phantasmatic objectivity called ideology. Investigating this concept reveals its various nuances, its explicit and hidden double, its ideological and jouissance bias, its relationship with the subject of the unconscious, its links with fetishism and the a-object, and its importance for social criticism and its repercussions on the analysis of the virtual reality that has completely taken hold in the 21st century. Ideological fantasy is also important for psychoanalysis when articulated with the Lacanian formulation of the graph of desire, its relationship with Freud's concept of reality and its contributions to the debate on the formation of the self and the subject in Lacan. As a result, it is considered that the concept studied contributes not only to the analysis of social phenomena, but also to psychoanalytic research itself, creating new paths for the investigation of social phenomena based on the concepts of psychoanalysis itself.